PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN SOFTWARE LECTORA INSPIRE PADA MATERI PERBANDINGAN UNTUK SISWA KELAS VII SMP - Mahmudah, Rivadatul; Ahyan, Shahibul; Rasidi, Ahmad (Universitas Papua, 2018)
This research aim to develop the media of mathematics teaching using lectora inspire software in proportion material. This research was conducted as the research development, such as: visual aspect and audio, languages, the effect of use teaching strategies and material aspect. This research was involved the media expert, material expert and students’ response to conduct the research. Totally the media was developed showing the excellent criteria, it is 97% score based on the media expert and 86% based on the material expert. Based on the student responses, it shows 76% as the good criteria. So that why, the researcher can be concluded that this media gave a positive effect for the user, based on the results of students with 74% score and it can be as the alternative media to conduct teaching learning process. DOI: https://doi.org/10.30862/jhm.v1i1.769